Effect of LncRNA-MALAT1 on mineralization of dental pulp cells in a high-glucose microenvironment - Li, Xinzhu; Xu, Wenan; Lin, Xiaoyu; Wu, Jingyi; Wu, Buling (Frontiers in Cell and Developmental Biology, 2022)
Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) belongs to the long non-coding RNA (LncRNA) family. The LncRNA-MALAT1 is expressed in a variety of tissues and involved in a variety of diseases and biological processes. Although LncRNA-MALAT1 is up-regulation in the high glucose microenvironment and may participates in odontogenic differentiation, the underlying mechanism is not yet well elucidated. Here, we show that MALAT1 was mainly expressed in the cytoplasm of dental pulp cells (DPCs) in situ hybridization. In addition, high levels of mineralization-related factors, namely, tumor growth factor β 1 and 2 (TGFβ-1 and TGFβ-2), bone morphogenetic protein 2 and 4 (BMP2 and BMP4), bone morphogenetic protein receptor 1 (BMPR1), SMAD Family Member 2 (SMAD2), runt-related transcription factor 2 (RUNX2), Msh homeobox 2 (MSX2), transcription factor SP7 (SP7), alkaline phosphatase (ALP), dentin matrix acidic phosphoprotein 1 (DMP1), and dentin sialophosphoprotein (DSPP), were expressed, and MALAT1 was significantly overexpressed in DPCs at 7 and 14 days after mineralization induction in a high-glucose microenvironment, but only TGFβ-1, BMP2, MSX2, SP7, ALP, and DSPP were significantly downregulated in DPCs after MALAT1 inhibition. MALAT1 may participate in the mineralization process of DPCs by regulating multiple factors (TGFβ-1, BMP2, MSX2, SP7, ALP, and DSPP).